Izkušnje medicinskih sester z medpoklicnim sodelovanjem - Trpin, Simona (Obzornik zdravstvene nege, 2026)
Introduction: Nurses collaborate with various healthcare professions. This study aimed to determine how nurses experience collaboration between different professional groups at all three levels of health care and how they perceive the importance of interprofessional collaboration.Methods: This study adopted a qualitative research methodology. The sample consisted of 9 nurses working at the primary, secondary, and tertiary levels of health care. Semi-structured individual interviews were conducted in December 2023. Data were analysed using content analysis of the interview transcripts.Results: Four thematic categories were identified describing the phenomenon under investigation: (1) The importance of interprofessional collaboration, (2) Personal experiences, (3) The importance of communication in interprofessional collaboration, and (4) Measures to improve interprofessional collaboration.Discussion and conclusion: The primary challenge for interprofessional collaboration in health care is securing adequate coaching and fostering mutual respect, especially between professionals with varying levels of training. The results of this study suggest that while relationships in interdisciplinary teams are good, problems tend to become increasingly pronounced in higher-level occupational roles. Further research should focus on training in collaboration and communication, including all healthcare professions, not exclusively nursing.
Keywords: impact; medicinske sestre; nurses; profesionalnost; professionality; role; satisfaction; vloga; vpliv; zadovoljstvo